Insilico analyses of heparin binding proteins expression in human periodontal tissues. (December 2016) - Lackey, Bernadette; Nunes, Quentin; Higham, Susan; Fernig, David; Valappil, Sabeel
Abstract Background Periodontitis is described as a group of inflammatory diseases of the gingiva and supporting structures of the periodontium. The accumulation of plaque bacteria, which include putative periodontal pathogens, is known to initiate the disease but the host immune response is the major contributing factor for destruction of periodontal tissues. Proteins that bind to heparin heparin-binding protein (HBPs) play important roles in health and disease and interact with each other via networks known as 'heparin interactomes'. This study aimed at evaluating published datasets of HBPs and its role in periodontitis. Methods To elucidate the role of HBPs in periodontitis, bioinformatics analyses of published data was used.In silico analyses of published datasets were used to construct a putative HBPs interactome using an online database resource, 'STRING' (Search Tool for the Retrieval of Interacting Genes). Results PubMed searches identified 249 genes that were up regulated and 146 genes that were down regulated in periodontal disease, compared with periodontal disease-free gingival samples.In silico analyses using published datasets revealed 25 up-regulated and 23 down-regulated HBPs in periodontitis. Of these HBPs; chemokines, such as CXCL12 was up regulated where as some of the matrixmetalloproteinases (MMPs; MMP-2 and MMP9) were up-regulated while MMP-14 was down regulated. Conclusions The results indicate that HBP analyses will provide multiple targets for the biological mechanisms underlying periodontal disease (such as MMPs, cytokines and chemokines) that will have important clinical implications in the future drug design and management of periodontal disease.